2017
DOI: 10.1002/csr.1464
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility Excites ‘Exponential’ Positive Employee Engagement: The Matthew Effect in CSR and Sustainable Policy

Abstract: Corporate social responsibility (CSR) captures an organization's commitment to and engagement with multiple stakeholders; integrates economic, social, and environmental concerns into sustainable policies; and enhances employee perceptions, emotions, long-term value creation, and financial success. Most researchers have reported linear relationships between CSR and employee attitudes. Here, we test a new theory: After surpassing an upper bar, employee-perceived CSR exponentially stimulates their organizational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 98 publications
(131 reference statements)
1
95
0
Order By: Relevance
“…Zhou, Luo, and Tang () tested the theory that “perceived CSR exponentially excites job satisfaction through organizational pride,” which was supported by data collected from 296 managers and employees in 12 different companies in China. In the United States, Block, Glavas, Mannor, and Erskine () examined the positive impact that corporate philanthropy has on the organization's employees and investigated how such efforts can be managed strategically to maximize their impact.…”
Section: Literature Related To the Impact Of Csr On Eesupporting
confidence: 94%
“…Zhou, Luo, and Tang () tested the theory that “perceived CSR exponentially excites job satisfaction through organizational pride,” which was supported by data collected from 296 managers and employees in 12 different companies in China. In the United States, Block, Glavas, Mannor, and Erskine () examined the positive impact that corporate philanthropy has on the organization's employees and investigated how such efforts can be managed strategically to maximize their impact.…”
Section: Literature Related To the Impact Of Csr On Eesupporting
confidence: 94%
“…The importance of individuals' attitudes for employer attractiveness has already been demonstrated by Klimkiewicz and Oltra (2017), who showed that attitudes toward an organization's corporate social responsibility (CSR) influence how job seekers interpret information related to a company's CSR and eventually the perceived attractiveness of the organization. This reasoning is further supported by Zhou, Luo, and Tang (2017), who found that after surpassing a certain threshold, CSR exponentially increases organizational pride, job satisfaction and affective commitment (through organizational pride). These beneficial effects may relate to employees' viewing their organizations in a different light when CSR performance is high, as it evokes positive emotions and organizational satisfaction (Onkila, 2015).…”
Section: Introductionmentioning
confidence: 65%
“…This analysis is important for at least three reasons. Christmann & Taylor, 2006;Ciliberti et al, 2009;Zhou, Luo, & Tang, 2017). Second, the study sheds more light on the outcomes of certifiable standards for CSR.…”
Section: Introductionmentioning
confidence: 93%